PENGARUH METODE MICRO ROLE PLAYING TERHADAP INTERAKSI SOSIAL ANAK USIA 5-6 TAHUN DI TK KARTISA KABUPATEN BANYUASIN - Dwi Anugrah, Shinta; Suningsih, Taruni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social interaction is a crucial aspect of early childhood development, as it plays an important role in shaping children’s ability to engage in social contact, communicate, understand positive and negative social attitudes, and demonstrate appropriate behavior in group activities. This study aims to determine the effect of the Micro Role Playing method on the social interaction of children aged 5–6 years at TK Kartisa, Banyuasin Regency. The research problem is the low ability of children in communication, sharing, cooperation, and participation in group activities. This study employed a quantitative approach with a pre-experimental design using a one-shot case study on 14 children in class B1 selected through purposive sampling. Data were collected through observation using an assessment rubric and documentation, which included indicators of social interaction based on four aspects: social contact, communication, attitude, and behavior, with valid and reliable instruments. Data analysis was conducted using a normality test and a one-tailed t-test. The results showed that the data were normally distributed and the hypothesis test indicated that (4.80 ≥ 1.771), meaning that the Micro Role Playing method has an effect on children’s social interaction. This is reflected in the children’s ability to engage in social contact, communicate, recognize positive and negative attitudes, and demonstrate appropriate behavior in group settings. Therefore, the Micro Role Playing method is effective as a learning approach that influences the social interaction of children aged 5–6 years, particularly in the aspects of social contact, communication, attitude, and behavior.